Implantacion de la contabilidad comercial en la empresa “Farmacia Santa Fe sucursal 2” en la ciudad de Loja, periodo octubre del 2013 - Samaniego Berru, Vanesa Mireya (2014)
This paper deals with theoretical and practical "PHARMACY BRANCH SANTA FE 2" in order to improve their economic performance, and is structured according to the requirements and regulations of the National University of Loja, to obtain the title of Engineer in Accounting CPA Auditor CPA Audit. Finally it could be concluded that the proposed objectives were achieved where the accounting process developed from the chart of accounts until the financial statements, also lifting inventory of pharmaceutical and medicinal products was obtained; source documents such as invoices, withholding, etc..; accounting entry formats of information according to the need of pharmacy were developed. Thus the owner manager is suggested to take into account the accounting proposal and its immediate implementation, thus will have an orderly to control their movements and get a balance at any time in order to safeguard the resources to improve their economic solvency inventory.